Key Points in the Determination of the Interfacial Dzyaloshinskii-Moriya Interaction From Asymmetric Bubble Domain Expansion - Magni, Alessandro; Carlotti, Giovanni; Casiraghi, A.; Darwin, E.; Durin, G.; Diez, L. Herrera; Hickey, B. J.; Huxtable, A.; Hwang, C. Y.; Jakob, Gerhard; Kim, C.; Klaui, M.; et al. (IEEE Transactions on Magnetics, 2022)
Different models have been used to evaluate the interfacial Dzyaloshinskii-Moriya interaction (DMI) from the asymmetric bubble expansion method using magneto-optics. Here, we investigate the most promising candidates over a range of different magnetic multilayers with perpendicular anisotropy. Models based on the standard creep hypothesis are not able to reproduce the domain wall (DW) velocity profile when the DW roughness is high. Our results demonstrate that the DW roughness and the interface roughness of the sample layers are correlated. Furthermore, we give guidance on how to obtain reliable results for the DMI value with this popular method. A comparison of the results with Brillouin light scattering (BLS) measurements on the same samples shows that the BLS approach often results in higher measured values of DMI.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Domain structures; Dzyaloshinskii-Moriya interaction (DMI); magneto-optics